6-Bromo-1,3-di-2-propynyl-1H-imidazo[4,5-b]pyridin-2(3H)-one - Dahmani, S.; Haoudi, A.; Capet, F.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The room-temperature reaction of propargyl bromide and 6-bromo-1,3-dihydroimidazo[4,5-b]pyridin-2-one in dimethylformamide yields the title compound, C(12)H(8)BrN(3)O, which features nitrogen-bound propynyl substituents. The imidazopyridine fused ring is almost planar (r.m.s. deviation = 0.011 angstrom); the propynyl chains point in opposite directions relative to the fused ring. One acetylenic H atom is hydrogen bonded to the carbonyl O atom of an inversion-related molecule, forming a dimer; adjacent dimers are linked by a second acetylene-pyridine C-H center dot center dot center dot N interaction, forming a layer motif.